Effects of metformin on fibroblast growth factor 21 in patients with type 2 diabetes mellitus: faraway but so close - Hayder M. Al-kuraishy; Ali I. Al-Gareeb; Majid S. Jabir; Salim Albukhaty (SpringerOpen, 2023)
Abstract Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder characterized by insulin resistance (IR) and hyperglycemia. The development of inflammatory disorders in T2DM triggers the activation of different growth factors as a compensatory mechanism to reduce IR and adipose tissue dysfunction in T2DM. Fibroblast growth factor 21 (FGF21) which is involved in the regulation of glucose homeostasis is attractive to be a novel therapeutic target in the management of T2DM. FGF21 has poor pharmacokinetic profile as it rapidly degraded; therefore, FGF21 analogs which are more stable can be used in T2DM patients. However, FGF21 analogs are tested pre-clinically but not approved in clinical settings. Therefore, searching for anti-diabetic agents who enhance FGF21 expression is mandatory. It has been shown that metformin which used as a first-line in the management of T2DM can positively affect the expression of FGF21, though the underlying mechanisms for metformin-induced FGF21 expression are not fully elucidated. Therefore, this review from published studies aimed to find how metformin improves insulin sensitivity through FGF21-dependent pathway in T2DM. In conclusion, metformin improves FGF21 signaling in T2DM, and this could be a novel mechanism for metformin in the amelioration of glucose homeostasis and metabolic disorders in T2DM patients.